A Just Transition for Auto Workers? Negotiating the Electric Vehicle Transition in Germany and North America - Mathieu Dupuis; Ian Greer; Anja Kirsch; Grzegorz Lechowski; Dongwoo Park; Tobias Zimmermann (ILR Review, 2024)
Reducing human-made greenhouse gas emissions is crucially important for life on earth, but it requires restructuring industries in ways that could disrupt millions of workers' lives globally. Whether this transition is “just” from the perspective of workers depends on the magnitude of job losses, the quality of new jobs, and the transitions workers experience from their current jobs to new ones. Using the example of the German automotive industry, where the shift to electric vehicle production has recently accelerated, the authors identify recommendations for unions and policymakers in North America and beyond. This article provides an overview of the tools for workers and trade unions in Germany to steer the transition and shows how analogous tools could be strengthened or created elsewhere.
Keywords: 330; just transition; environmental restructuring; comparative industrial relations; policy proposals; union management relationship; collective bargaining